PENGARUH INTENSITAS ANAK MENGAKSES GADGET DAN TINGKAT KONTROL ORANGTUA ANAK TERHADAP INTERAKSI SOSIAL ANAK SD KELAS TINGGI DI SD 1 PASURUHAN KIDUL KUDUS JAWA TENGAH - Faiz Noormiyanto (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2018)
The purpose of this study was to determine the effect of children's access intensity andparental control level of children to social interaction of high school elementary children in SD 1pasuruhan kidul kudus of central jawa. This research was conducted by selecting three classes,namely Class Six, four, and Five class. The research method used is survey research type usingquantitative approach. Data collection techniques used documentation and questionnaires. Theinstrument used in this research is questionnaire. As for the analysis of the results is using thefirst test prerequisite analysis consisting of normality test, homogeneity test and multiple linearregression on the test of research hypothesis. The results of this study is the intensity ofaccessing the gadget has a significant effect on social interaction of high class students, parentalcontrol has a significant influence on student social interaction and the intensity of accessingGadgets and parental control together have a significant effect on student social interaction Thisstudy will have an impact on the awareness of parents and teachers about the dangers of the useof Gadget in children intensely or excessively will affect the social interaction of children withempirical evidence about the linkage between the intensity of accessing Gadget and parentalcontrols to the social interaction of children, this research can provide theoretical contributionwith become a reference in improving the quality of schools in accordance with the developmentof the times by limiting and providing direction to parents to limit access and use of Gadgetsamong students. Benefits for lecturers that can encourage lecturers to be more creative indeveloping and utilizing gadgets or smartphones in learning so that the learning outcomesincrease, see from the intensity of students using gadgets and create a model of learning mediadevelopment using gadgets. In addition, the impact for students is that students can improvecreativity in using learning media that is in accordance with the interests of students, especiallyin the field of information technology.Key Words : Intensity, Gadgets, Parental Controls, Social InteractionsÂ